THE LITURGY OF THE MAR THOMA SYRIAN CHURCH OF MALABAR IN TH E LIGHT OF ITS HISTORY - ZACHARIA JOHN (University of Durham, 1994)
This thesis is an evaluation of the Divine Liturgy of the Mar Thoma Syrian Church, from a historical perspective. The Mar Thoma Syrian Church of Malabar, as it is officially known, is an Oriental Reformed Church with its head quarters at Tiruvalla in Kerala State, the south west coast of India. The Christians of Kerala are known as Syrians, owing to their descent from the immigrants of Persia and through the use of the Syrian liturgy as well. The first chapter gives the common history of the Syrian Christian community of Kerala. Owing to the change of the Western political powers that ruled India from time to time, this community has been fragmented into different Christian denominations. It ipso-facto adopted different liturgies viz. the Chaldean (East Syrian), Roman (Latin), Antiochian (West Syrian), Anglican etc. Only Antiochian liturgy comes in the scope of this study. The second chapter describes the different stages of the Antioch&an connection and the distinctive features of its liturgy. Tradition and renewal are not contrary but complimentary. Tradition enables to become part of the past and renewal helps to be relevant. Negation of either results in imbalance. The touch-stone of the two is to be the Scripture. The third chapter describes the impact of the Scripture in the Syrian Reformation of the 19th century and the fourth chapter, the consequent developments in the Syrian Church. The fifth chapter gives the different stages of the liturgical revisions in the Mar Thoma Church. The sixth chapter shows that the said Reformation was an earnest endeavour of correction rather than abolition. It resulted in the revision of the Antjochian liturgy at certain points. Like the other Eastern and Oriental Churches the doctrines of the Mar Thoma Church are also embedded in its liturgy. The liturgy proves its accordance with the Scriptures and Canons.